Accessibility Guidelines for VR Games - A Comparison and Synthesis of a Comprehensive Set - Heilemann, Fiona; Zimmermann, Gottfried; Münster, Patrick (Frontiers in Virtual Reality, 2021)
Increasing numbers of gamers worldwide have led to more attention being paid to accessibility in games. Virtual Reality offers new possibilities to enable people to play games but also comes with new challenges for accessibility. Guidelines provide help for developers to avoid barriers and include persons with disabilities in their games. As of today, there are only a few extensive collections of accessibility rules on video games. Especially new technologies like virtual reality are sparsely represented in current guidelines. In this work, we provide an overview of existing guidelines for games and VR applications. We examine the most relevant resources, and form a union set. From this, we derive a comprehensive set of guidelines. This set summarizes the rules that are relevant for accessible VR games. We discuss the state of guidelines and their implication on the development of educational games, and provide suggestions on how to improve the situation.